Primary health care for all: lessons from its failure to achieve its goal and COVID-19 - Yusuf, Erlangga (Universa Medicina, 2021)
According to the World Health Organization (WHO), primary health care (PHC) can be defined as a whole-of-society approach to health and well-being, centered on the needs and preferences of individuals, families and communities. In the last five years, several major events occurred that emphasize the importance of and the need for PHC. First, the publication of the United Nations Sustainable Development Goals (SDGs) in 2015. One of the SDGs is to achieve universal health care (UHC). UHC means that all people can get access to health service without it resulting in financial hardship, and  the WHO believes that PHC is fundamental to achieving UHC. Second, a new international declaration on PHC has been released in Astana, Kazakhstan, in 2018. This is a new declaration and global commitment on PHC, four decennia after the first declaration on PHC in Alma-Ata, in the former Soviet Union